EVALUASI PENYIMPANAN VAKSIN BERDASARKAN PRINSIP SYARIAT ISLAM DI PUSKESMAS MANYARAN KOTA SEMARANG - Wijayanti, Rina; Yulianti, Beti; Saraswati, Herluin Nadia (As-Syifaa Jurnal Farmasi, 2024)
Vaccine management at the health Center still needs special attention where it is known that there are still many cold chain managements, especially vaccines, which have not been managed properly so that there is a lot of damage to the vaccine. The purpose of this study is to determine the description of the suitability and evaluation of vaccine storage based on the principles of Islamic law at Manyaran Health Center, Semarang City. The variable used in this study is a single variable with observations related to vaccine storage, facilities and infrastructure, refrigerator conditions (cold chain management) at Manyaran Healt Center using a checklist sheet for observation. The results showed that each evaluation of vaccine storage, facilities and infrastructure, and the state of the refrigerator at Manyaran Health Center in Semarang City was categorized as good with a percentage of 100%.